(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Current reality shows an increase in various problems afflicting society. This scenario is worrying and can jeopardise as well negatively affect human wellbeing. Islam emphasises a comprehensive development of human life without neglecting other aspects. One of these types of developments is human development (HD). Understanding the Islamic-based human development (IbHD) should be emphasised in order to implement a sustainable life. Hence, this study intended to identify the IbHD concept as well as its significance. This study employed the document research method for data collection by applying the content analysis approach for analysing data. Findings show that IbHD differs from conventional development (CD) because IbHD uses a development model outlined by the Quran and Sunnah, multi-dimensional, own its unique principles, also playing an important fundamental element in building quality humans in this world and in the afterlife.